DOP10 Serum N-glycomic biomarkers predict treatment escalation in inflammatory bowel disease. (25th January 2019) - Shubhakar, A; Jansen, B; Adams, A; Reiding, K; Ventham, N; Bergemalm, D; Urbanowicz, P; Gardner, R; ,; Halfvarson, J; Satsangi, J; Fernandes, D; et al.
Abstract: Background: Biomarkers to predict treatment response would be highly beneficial in the clinical management of inflammatory bowel disease (IBD). To that end we have investigated the validity of a composite N-glycomic biomarker from 10 µl of serum taken at diagnosis. Methods: An automated high-throughput fluorescent labelling of total serum N-glycans (TSNG) from 227 patients and 195 controls from Edinburgh (UK) was performed using ultra-high-performance liquid chromatography (UHPLC). Forty-seven individual glycan peaks were integrated consisting of 105 glycoforms and structurally related glycans were used to create 24 derived glycan traits. Cox proportional hazard models was used to determine prediction of treatment escalation to anti-TNF, biologics, and surgery. A replication cohort of 49 patients (15 requiring treatment escalation) was recruited in Orebro (Sweden) to validate the escalation biomarker. Additionally, logistic regression analysis was performed to determine associations of glycomics with IBD and clinical markers. Results: The glycomics biomarkers for treatment escalation gave a hazards ratio (HR) of 23.73 ( p = 6.81 × 10 −06 ) for CD and an HR of 30.83 ( p = 1.88 × 10 −04 ) for UC. A composite marker for all IBD patients gave an HR of 25.91 ( p = 1.12 × 10 –12 ) using the discovery cohort (Panel A). This composite IBD biomarker was further validated in an independent replication cohort with an HR of 5.07 ( p = 1.14 × 10 –5 ) (Panel B). Additionally, changes (Bonferroni, α < 0.05) in glycosylation-derived traits were associated with IBD ( n = 13), as well as with clinical parameters ( n = 18). Conclusions: Serum N-glycan signatures were shown to predict the need for treatment escalation in patients with CD or UC separately or all IBD patients. Therefore, serum N-glycan biomarkers could help deliver personalised treatment of IBD.